DAUR ULANG AIR SISA PROSES RELAKSASI-PENGHILANGAN KANJI-PEMASAKAN (SIMULTAN) DENGAN CARA KOAGULASI-FLOKULASI MENGGUNAKAN POLY ALUMINIUM CHLORIDE (PAC) UNTUK DIMANFAATKAN KEMBALI SEBAGAI AIR PROSES YANG SAMA DI PT. DX TEKSTIL BANDUNG - Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
To overcome the problem of the limited supply of process water because of its dependence on groundwater due to reducing its discharge, stricting provision of government permits in the depthening of bore wells and increasing the cost of retribution for extracting groundwater, an experimental investigation was conducted to explore the possibility of recycling waste water from the preparation textile process namely Relaxing-Desizing-Scouring (simultaneous), in order to be reused as water for similar process and moreover for dyeing process possibility. The method was coagulation-floculation with Poly Aluminium Chloride (PAC) with concentration variation of PAC 0.5; 0.7; 0.9; 1.1; 1.3; 1.5 (g/l) analyzed, in condition pH 8 where larger floc size is produced at pH 7-9 (Taki Chemical Co.LTD, 1992), and continuing with testing COD, BOD, pH, total hardness, total suspended solid (TSS), chloride levels, and turbidity. In this study, the optimum PAC concentration was obtained, which was 1.3 g / l to meet the requirement. The further process was conducted both Relaxing-Desizing-Scouring (simultaneous) and dyeing by using water after treatment, before treatment and waterground from factory to be compared their results. And to determine the success of the water treatment, tests for weight reduction, white degrees and color differences were carried out. Keywords: Coagulation-Floculation, recycling, waste water, Poly Aluminium Chloride